براہوئی ادب میں ترجمہ نگاری : Translation in Brahui Literature - Rodeni, Yousaf Ali (Al-Burz, 2011)
This article shares the basic and primary information about the translated literature in Brahui language. It reveals that before Brahui fiction the translation has played its vital role to strengthen the Brahui literature. Basic religious knowledge has been translated in to Brahui language. Translation has been promoted in large scale in period of Maktaba. This article informs that the subject of translation has observed in old and modern Brahui literature. In modern literature the requirements of translation are different than the old one. Now the fiction and short stories of world’s well-known writers are being translated in Brahui. Which increased the importance of translation in literature and translation is being taught as a separate subject in Brahui. Descriptive study has been adopted for this article finally it ends with the justified and fruitful recommendations that translator must aware from source and targeted languages, their formations, language structure and grammar.